2020
DOI: 10.1101/2020.07.22.216614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meiotic sister chromatid exchanges are rare inC. elegans

Abstract: Sexual reproduction shuffles the parental genomes to generate new genetic combinations. To achieve that, the genome is subjected to numerous double-strand breaks, the repair of which involves two crucial decisions: repair pathway and repair template. Use of crossover pathways with the homologous chromosome as template exchanges genetic information and directs chromosome segregation. Crossover repair, however, can compromise the integrity of the repair template and is therefore tightly regulated. The extent to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In addition to bringing homologs together, pro-crossover factors are recruited to the SC, and in that way the SC limits crossovers to synapsed chromosomal regions. This idea receives support in this work, where we show that the SC that assembles on unpaired axes in syp-1 K42E (25°C) animals can recruit GFP-COSA-1 (see also [ 6 , 41 ]). Our work also strengthens the idea that, at least in C .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition to bringing homologs together, pro-crossover factors are recruited to the SC, and in that way the SC limits crossovers to synapsed chromosomal regions. This idea receives support in this work, where we show that the SC that assembles on unpaired axes in syp-1 K42E (25°C) animals can recruit GFP-COSA-1 (see also [ 6 , 41 ]). Our work also strengthens the idea that, at least in C .…”
Section: Discussionmentioning
confidence: 60%
“…This was particularly striking in the case of syp-1 K42E (25°C) animals, where despite lack of homolog zipping, and hence of actual crossovers, we observed an average of 16.4 GFP-COSA-1 foci per nucleus ( Fig 5A–5C ). Based on observations of differentially labeled sister-chromatids, at least some of these foci likely mark inter-sister exchanges [ 41 ]. Tracing of GFP-COSA-1 foci in syp-1 Δ8 animals indicated that the increased overall foci number is not due to association of multiple foci per chromosome–like in wild-type animals, every chromosome harbors only a single focus–but likely due to association of foci with the SC on both zipped and unzipped chromosomes ( Fig 5A–5C ).…”
Section: Resultsmentioning
confidence: 99%
“…2011; ROSU et al . 2011; S eidel and K imble 2015; A lmanzar et al . 2021).…”
Section: Resultsmentioning
confidence: 99%
“…EdU staining was performed as described in (A lmanzar et al . 2021) with minor changes.…”
Section: Methodsmentioning
confidence: 99%